2015
DOI: 10.15537/smj.2015.12.12622
|View full text |Cite
|
Sign up to set email alerts
|

Dental knowledge of educators and healthcare providers working with children with autism spectrum disorders

Abstract: Objectives:To evaluate dental knowledge and attitudes toward oral health care among healthcare providers and educators working with children with autism spectrum disorders (ASD) in central Saudi Arabia.Methods:There were 305 questionnaires distributed to 7 special-needs centers between September and November 2014. A total of 217 questionnaires were collected with a response rate of 71.1%. The study took place in the College of Dentistry, King Saud University, Riyadh, Kingdom of Saudi Arabia.Results:Approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
11
0
2
Order By: Relevance
“… 1 , 3 , 7 , 13 , 16 , 19 , 22 24 , 26 30 These studies attempted to measure the preparedness, 9 , 13 , 26 , 27 experience, 19 , 22 , 23 , 26 , 27 knowledge, 3 attitudes, 13 , 26 , 29 and perceptions 7 , 24 , 31 of the dental care providers in regard to treating patients with special needs. The studies were directed at different target populations, where some targeted decision makers at dental teaching institutions, 1 , 3 , 27 while others targeted clinical dental care providers 29 – 32 and some studies targeted alumni and/or current students. 7 , 13 , 19 , 22 24 , 26 , 28 …”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 , 3 , 7 , 13 , 16 , 19 , 22 24 , 26 30 These studies attempted to measure the preparedness, 9 , 13 , 26 , 27 experience, 19 , 22 , 23 , 26 , 27 knowledge, 3 attitudes, 13 , 26 , 29 and perceptions 7 , 24 , 31 of the dental care providers in regard to treating patients with special needs. The studies were directed at different target populations, where some targeted decision makers at dental teaching institutions, 1 , 3 , 27 while others targeted clinical dental care providers 29 – 32 and some studies targeted alumni and/or current students. 7 , 13 , 19 , 22 24 , 26 , 28 …”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the reviewed scales were self-developed by the authors, 16 , 23 , 26 , 27 while others adapted scales from the literature, 22 , 29 , 30 , 32 and most of the reviewed studies did not mention the development of their scales.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant difference between the information regarding the families and the children clearly indicate the need for education programs aiming to encourage the adherence to hygienic habits of oral care by families and professionals working with ASD children ( 7 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in majority countries describe challenging realities. In Saudi Arabia, educators, families and health-care providers tend to neglect oral-health care when working with children with ASD ( 9 , 10 ). A research about dental care experiences of children with ASD in three major cities in Saudi Arabia ( 11 ) concluded that more than half of the children had no previous dental-care experience and 33% of them were treated under general anesthesia.…”
Section: Introductionmentioning
confidence: 99%